Penerapan Metode Cerita terhadap Pembentukan Karakter Religius Siswa pada Pelajaran PAI Kelas VII SMPN 3 Jombang - Wahyudi Wahyudi; Nur Chasib (Institut Agama Islam Sumatera Barat, 2023)
Lately in the world of education, especially for students, there are still many problems faced by teachers in shaping the character of their students according to what is expected by the curriculum or education in Indonesia, how can an institution/school shape the character of its students to become good personalities so that in the study In this study, the researcher will try to review a learning method, more precisely the story learning method, especially in Islamic religious education subjects in the hope of forming student character with a good personality. In this study, the researcher used a qualitative research method in which the researcher was present in the process of implementing the story method. in class VII SMPN 3 Jombang so that the data from the results of this study are truly authentic as it is, after using the story method in the learning process it has shown students' understanding of the material they have received and most students are able to apply the contents of the material content conveyed by the story method both in everyday life in the school environment and in the family.